Early Rome : myth and society : a sourcebook - Neel, Jaclyn; Neel, Jaclyn (Hoboken, New Jersey, USA : J John Wiley & Sons, Inc., 2017)
The scholarly community has become increasingly aware of the differences between Roman myths and the more familiar myths of Greece. Early Rome: Myth and Society steps in to provide much-needed modern and accessible translations and commentaries on Italian legends. This work examines the tales of Roman pre-and legendary history, discusses relevant cultural and contextual information, and presents author biographies. This book offers updated translations of key texts, including authors who are often absent from classical mythology textbooks, such as Dionysius of Halicarnassus and Servius. Editor Jaclyn Neel debunks the idea that Romans were unimaginative copyists by spotlighting the vitality and flexibility of Italian myth, particularly those parts that are less closely connected to Greek tales, such as the story of Caeculus of Praeneste. Finally, by calling attention to the Italian rather than Roman nature of the collection, this book suggests that Roman culture was broader than the city itself. This important work offers: Up-to-date and accessible translations of Roman and Italic legends from authors throughout antiquity ; Examination of compelling tales that involve the Roman equivalent of Greek 'heroes' ; Unique view of the strength and plasticity of Roman and Italic myth, particularly the parts less closely connected to familiar Greek tales ; Intelligent discussion of relevant cultural and contextual information Argument that Roman culture reached far beyond the city of Rome Fresh and readable, Early Rome: Myth and Society offers essential reading for students of ancient Rome as well as those interested in Roman and Greek mythology. - Publisher.
Preface xi Abbreviations & Symbols xv 1 Introducing Early Rome 1 Introduction 1 1.1 What Is a Myth ? 2 1.2 Types of Stories You Will Read in this Book 4 1.3 Literary Genres in this Book 7 1.4 Theoretical Approaches to Roman Myth 10 1.5 Chronology of Early Rome 11 Conclusion 14 Notes 14 References 14 Further Reading 15 2 Rome Before the City 17 Introduction 17 For Further Thought 20 2.1 The Earliest Italians 20 2.2 Inhabitants of the Site of Rome 26 2.3 Aeneas in Italy 32 2.4 Aeneas Arrival in Latium 34 2.5 War in Italy 37 2.6 The Death of Aeneas and Pater Indiges 43 2.7 Ascanius, Silvius, and Lavinia: the Alban Dynasty 45 Conclusion 49 Notes 50 References 53 Further Reading 53 3 Founding Rome 55 Introduction 55 For Further Thought 58 3.1 Conception, Birth, and Exposure 58 3.2 Youth of Romulus and Remus 65 3.3 Rome s Foundation 69 3.4 The Death of Remus 74 3.5 Wars with the Sabines 78 3.6 Death of Titus Tatius 86 3.7 Death and Apotheosis of Romulus 88 Conclusion 91 Notes 92 References 95 Further Reading 95 4 Images and Text 97 Introduction 97 For Further Thought 99 4.1 Mlacuch 99 4.2 Hercules and Juno 101 4.3 Suckling Wolf 104 4.4 Prophets 108 4.5 Wolfman 111 4.6 The Vibenna Brothers 113 4.7 Vulca of Veii 119 Conclusion 121 Notes 122 References 122 Further Reading 123 5 Rome s Kings 125 Introduction 125 For Further Thought 128 5.1 The Interregnum (717 716) 129 5.2 Numa (716 674) 130 5.3 Tullus Hostilius (673 642) 138 5.4 Tarquinius Priscus (616 578) 145 5.5 Servius Tullius (578 535) 155 5.6 Tarquin the Proud (534 509) 162 Conclusion 173 Notes 174 References 177 Further Reading 177 6 Italy Outside Rome 179 Introduction 179 For Further Thought 181 6.1 Greek Founders in Italy 181 6.2 Hercules 185 6.3 Diomedes in Italy 187 6.4 Myths of Locri 190 6.5 The Sacred Spring 194 6.6 Caeculus of Praeneste 196 6.7 Pomona and Vertumnus 197 Conclusion 199 Notes 200 References 201 Further Reading 201 7 Rome s Women 203 Introduction 203 For Further Thought 205 7.1 The Bona Dea 206 7.2 Women of the Aeneid 209 7.3 Acca Larentia 213 7.4 Tarpeia 215 7.5 Horatia 219 7.6 Lucretia 220 7.7 Cloelia 226 7.8 Verginia 228 7.9 Slave-women and the Nonae Caprotinae 230 Conclusion 231 Notes 232 References 234 Further Reading 234 8 Rome s Heroes 237 Introduction 237 For Further Thought 240 8.1 Brutus 240 8.2 Publicola 244 8.3 The War with Porsenna 246 8.4. Porsenna Captures Rome? 249 8.5 The Battle at Lake Regillus 250 8.6 Stories of Self-sacrifice for Rome 252 8.7 The 306 Fabii 254 8.8 The Conflict of the Orders 257 8.9 Camillus and Veii 262 8.10 The Gallic Sack 265 Conclusion 273 Notes 274 References 276 Further Reading 276 9 Conclusion 279 References 281 Appendix 1 Author Biographies 283 Appendix 2 Greek Mythical Characters 291 Appendix 3 Greek and Roman Gods 297 Index 299
HS
Includes bibliographical references and index.
Keywords: Mythology, Roman; Rome (Italy) -- History -- To 476 -- Sources; Italy -- History -- To 476 -- Mythology